2015
DOI: 10.1016/j.rbr.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Segurança do uso de terapias biológicas para o tratamento de artrite reumatoide e espondiloartrites

Abstract: The treatment of autoimmune rheumatic diseases has gradually improved over the last half century, which has been expanded with the contribution of biological therapies or immunobiopharmaceuticals. However, we must be alert to the possibilities of undesirable effects from the use of this class of medications. The Brazilian Society of Rheumatology (Sociedade Brasileira de Reumatologia/SBR) produced a document based on a comprehensive literature review on the safety aspects of this class of drugs, specifically wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 220 publications
(238 reference statements)
0
11
0
5
Order By: Relevance
“…Pharmacological agents known as anti-TNFα are able to block this inflammatory mechanism and may be used for SpA treatment. ( 8 )…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological agents known as anti-TNFα are able to block this inflammatory mechanism and may be used for SpA treatment. ( 8 )…”
Section: Introductionmentioning
confidence: 99%
“…The great advantage of this study is the consistent and complete LTBI screening for all patients using a standard protocol recommended by Brazilian guidelines ( 11 ) and the national recommendation for TB control ( 12 , 13 ). The non-homogeneous use of an LTBI screening protocol in previous studies hampers the interpretation of their findings on the relevance of each risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also highlighted a large frequency of infections and neoplasms. Other studies have also reported these ADRs as major safety concerns associated with the use of biologic drugs [9,28,35,36,[39][40][41]; however, there is still no consensus on the actual risk and the role of individual differences regarding these drugs, which suggests that these safety issues are still not well established and require further investigation [8,42].…”
Section: Discussionmentioning
confidence: 99%
“…The association between this event and use of infliximab was highlighted as an important safety concern, especially in autoimmune diseases. Although the number of reports associated with infliximab was low, careful and intensive monitoring of PML cases associated with biologics is needed [8,42]. Several SDRs were identified in only one subgroup of patients, what suggests that the use of disproportionality analyses by subgroups can help to identify groups with greater susceptibility to specific adverse events in addition to increasing the sensitivity for the detection of SDRs compared with crude or stratified analyses [31].…”
Section: Despite Belonging To the Same Class Of Drugs Tnfi Agents Prmentioning
confidence: 99%